Cyanophage-encoded lipid desaturases: oceanic distribution, diversity and function - Roitman, Sheila (ISME J, 2018)
Cyanobacteria are among the most abundant photosynthetic organisms in the oceans; viruses infecting cyanobacteria (cyanophages) can alter cyanobacterial populations, and therefore affect the local food web and global biochemical cycles. These phages carry auxiliary metabolic genes (AMGs), which rewire various metabolic pathways in the infected host cell, resulting in increased phage fitness. Coping with stress resulting from photodamage appears to be a central necessity of cyanophages, yet the overall mechanism is poorly understood. Here we report a novel, widespread cyanophage AMG, encoding a fatty acid desaturase (FAD), found in two genotypes with distinct geographical distribution. FADs are capable of modulating the fluidity of the host’s membrane, a fundamental stress response in living cells. We show that both viral FAD (vFAD) families are Δ9 lipid desaturases, catalyzing the desaturation at carbon 9 in C16 fatty acid chains. In addition, we present a comprehensive fatty acid profiling for marine cyanobacteria, which suggests a unique desaturation pathway of medium- to long-chain fatty acids no longer than C16, in accordance with the vFAD activity. Our findings suggest that cyanophages are capable of fiddling with the infected host’s membranes, possibly leading to increased photoprotection and potentially enhancing viral-encoded photosynthetic proteins, resulting in a new viral metabolic network.